Evaluation Of Profit Sharing Of Mukhabarah Contracts Based On Sharia Accounting Principles In Waempubbu Village, Amali District Bone - Nirwana Nirwana; Hartas Hasbi; Masyhuri Masyhuri (STAI Al-Mas'udiyah, 2026)
This study aims to evaluate the practice of profit sharing of mukhabarah contracts based on the principles of sharia accounting in the agricultural sector in Waempubbu Village, Amali District, Bone Regency. The focus of the research is directed at the mechanism for implementing profit sharing and its level of conformity with the principles of justice, honesty, transparency, and accountability in Shariah accounting. This study uses a descriptive qualitative approach with the type of field research. Data was obtained through interviews, observations, and documentation, then analyzed using the stages of data reduction, data presentation, and conclusions drawn. The results of the study showed that the implementation of the mukhabarah contract was carried out based on a verbal agreement between the landowner and the cultivator without a written agreement or formal recording. In practice, the landowner provides agricultural land, while the cultivator is responsible for the management until the harvest period, with a yield-sharing system according to the initial agreement. These practices have reflected the principles of fairness and honesty, but have not fully met the principles of transparency and accountability due to the absence of systematic recording of costs and results. Therefore, the implementation of simple recording and increased understanding of the principles of Sharia accounting are needed to realize a more transparent, fair, and accountable profit-sharing system.